Intestinal Parasites Infection in Children with Cancer in Ahvaz, Southwest Iran - Roya Salehi Kahyesh; Arash Alghasi; Shekoufe Haddadi; Asaad Sharhani (Interdisciplinary Perspectives on Infectious Diseases)
Background. Infection with intestinal parasites is widespread worldwide, especially in developing countries. Intestinal parasites are known as one of the leading causes of diarrhea in both immunocompetent and immunocompromised subjects, but cancer patients are highly susceptible to contamination, and it can be deadly for them. This study aimed to estimate the prevalence of intestinal parasites in immunocompromised patients in Ahvaz. Material and Methods. In this descriptive cross-sectional pilot case-control study, fecal samples were collected from 52 children with malignancies hospitalized in Baqaei2 hospital in Ahvaz. A questionnaire including demographic information, type of cancer, type of gastrointestinal symptoms, and laboratory diagnosis was completed for each patient. The collected specimens were examined by direct smear, Logul staining, and concentration. Result. The 52 stool samples were collected, 46% were female and 54% male. The age range of children enrolled in the study was from 4 months to 16 years. Of these stool samples, 38.38% were infected with a variety of parasitic intestinal infections (helminths and protozoa). In this study, protozoan parasites, Blastocystis (23%), Chilomastix mesnili (1.92%), Endolimax nana (7.7%), and Entamoeba coli (1.92%), and helminth infection, Strongyloides stercoralis (3.84%), were observed and statistical analysis showed that there was a significant relationship between gastrointestinal symptoms and parasitic infection in children with cancer. Conclusion. Blastocystis and Endolimax nana are the most prevalent gastrointestinal parasitic protozoans that infect individuals admitted to Baqaei2 Hospital of Ahvaz, Iran. Since parasitic intestinal infections in immunocompromised patients lead to fatal diarrhea, children with parasitic infections must be carefully identified and treated.